Adrenomedullin (ADM) in the human forearm vascular bed: effect of neutral endopeptidase inhibition and comparison with proadrenomedullin NH(2)-terminal 20 peptide (PAMP) - Wilkinson, Ian B (Blackwell Science Inc, 2001)
AIMS: To compare the haemodynamic responses of proadrenomedullin N-terminal 20 peptide (PAMP) and adrenomedullin (ADM) in the forearm vascular bed of healthy male volunteers, and to investigate the role of neutral endopeptidase (NEP) in the metabolism of ADM. METHODS: On two separate occasions, ADM (1–30 pmol min(−1)) and PAMP (100–3000 pmol min(−1)) were infused into the brachial artery of eight male subjects, and forearm blood flow (FBF) assessed using venous occlusion plethysmography. In a second study, eight male subjects received the same doses of ADM, co-infused with either the NEP inhibitor thiorphan (30 nmol min(−1)) or the control vasoconstrictor noradrenaline (120 pmol min(−1)), on separate occasions. Both studies were conducted in a double-blind, randomized manner. RESULTS: ADM and PAMP produced a dose-dependent increase in FBF (P ≤ 0.002). Based on the dose producing a 50% increase in FBF, ADM was ∼60 times more potent than PAMP. Thiorphan and noradrenaline produced similar reductions in FBF of 14 ± 4% (mean ± s.e. mean) and 22 ± 6%, respectively (P = 0.4). However, the area under the dose–response curve was significantly greater during co-infusion of ADM with thiorphan than with noradrenaline (P = 0.028), as was the maximum increase in FBF ratio (2.1 ± 1.0 vs 1.2 ± 0.2; P = 0.030). CONCLUSIONS: ADM and PAMP both produce a local dose-related vasodilatation in the human forearm, but PAMP is ∼60 times less potent than ADM. In addition, NEP inhibition potentiates the haemodynamic effects of ADM. These findings suggest that PAMP may not play a role in the physiological regulation of blood flow. However, in pathophysiological conditions such as hypertension and heart failure, NEP inhibition may exert a beneficial effect by increasing the biological activity of ADM.